2019
DOI: 10.1021/acsami.9b12626
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Preparation of a Highly Stretchable, Conductive, and Transparent Poly(vinyl alcohol)–Phytic Acid Hydrogel for Casual Writing Circuits

Abstract: Conductive hydrogels have shown great potential applications in a wide variety of fields, including artificial intelligence devices and biomedical engineering. However, it still remains a great challenge to develop a facile and cost-effective approach to achieve a conductive hydrogel with favorable qualities. Herein, we have changed the traditional ingredient of poly­(vinyl alcohol) (PVA) hydrogel by the addition of phytic acid (PA), which could yield a conductive hydrogel through one freeze–thaw cycle. The PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 50 publications
2
88
0
Order By: Relevance
“…2 C and Figure S2C ). The successful formation of hydrogels was confirmed by G′ > G″ [ [37] , [38] , [39] ]. We observed that the value of G′ decreased with the addition of PDA.…”
Section: Resultsmentioning
confidence: 99%
“…2 C and Figure S2C ). The successful formation of hydrogels was confirmed by G′ > G″ [ [37] , [38] , [39] ]. We observed that the value of G′ decreased with the addition of PDA.…”
Section: Resultsmentioning
confidence: 99%
“…In general, once the PVA hydrogels undergo the freezing-thawing process, the high crystallization of PVA polymer chains induced by the F-T process leads to a strong toughness but very low transparency. To improve the transparency, PVA hydrogels could be prepared via low-temperature crystallization using the mixed solvent (H 2 O/DMSO) [38]. However, the toxicity of DMSO and its difficulty to handle limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the black additives may also considerably impact on the optical transparency of hybrid hydrogels, causing less visual aesthetics and limiting their application scope. To solve above problems, traditional ionic conductive matters like salts, [ 11 ] ionic liquid, [ 11b,12 ] and small organic acid [ 13 ] have been attempted to introduce into the hydrogel matrix as well. Besides, the ionic conductive hydrogels always hold some other merits as anti‐freezing property and low volatility of water.…”
Section: Introductionmentioning
confidence: 99%